Glutamine Synthetase (GS): A Key Enzyme for Nitrogen Assimilation in The Macroalga Gracilariopsis lemaneiformis (Rhodophyta). Issue 5 (31st July 2019) - Liu, Xiaojuan; Huan, Zhongyan; Zhang, Qingfang; Zhong, Mingqi; Chen, Weizhou; Aslam, Muhammad; Du, Hong
Abstract : This study aimed to address the importance of glutamine synthetase II (GSII) during nitrogen assimilation in macroalga Gracilariopsis lemaneiformis . The cDNA full‐length sequence of the three glGSII genes was revealed to have the 5′ m 7 G cap, 5′‐untranslated region, open reading frame (ORF), 3′‐untranslated region, and a 3′ poly (A) tail. The three glGSIIs were classified into plastid glGS2 and cytosolic glGS1‐1 and glGS1‐2, having conserved GSII domains but different cDNA sequences. The complicated 5′ end flanking region indicates complex function of glGS genes. glGS1 genes were significantly up‐regulated under the different NH4 + : NO3 − ratio (i.e., 40:10, 25:25, 10:40, and 0:50) except glGS2 which dramatically up‐regulated under the low NH4 + : NO3 − ratio (i.e., 10:40 and 0:50) during different cultivation times. These different expression patterns perhaps are due to the different biological roles of GS1 and GS2 in the gene family. Furthermore, hypothetical working model of nitrogen assimilation pathway exhibiting the role of glGS1 and glGS2 is proposed. Finally, glGS2 was expressed in Escherichia coli BL21 (DE3), and the optimal conditions for culture (15°C, overnight), purification (500 mM imidazole washing), and activity (pH 7.4, 37°C) were established. This study lays a very important foundation for exploring the role of GS in nitrogen assimilation in algae and plants.